The Strength of Electronic Evidence in the View of Islamic Law - Enden Haetami (International Journal of Science and Society, 2022)
Electronic documents are admissible as evidence under Law No. 11 of 2008 about Electronic Information and Transactions; consequently, it is vital to examine the use of electronic documents as evidence in positive Indonesian law and how electronic evidence is seen in Islamic law. Al-Qur'an and As-Sunnah have specified the requirements for criminal proof in Islamic law. This is normative juridical research pertaining to legal norms and regulations, court decisions, and living norms that arise in society. According to the findings of the study, electronic media can be utilized as evidence, but not as standalone proof. In the Islamic legal system, electronic proof is accomplished by qarinah/guidance, next creed/witness, and ultimately book/writing. Therefore, it is anticipated that this research will provide a theoretical addition to the subject of Islamic law so that the use of electronic media will no longer be a legal issue and the public would be able to continue using them as evidence.